Standardization in the management of gram-negative bloodstream infections after implementation of a clinical care guideline at a large academic, safety-net institution: a quasi-experimental study - Michael A. Deaney; Katherine C. Shihadeh; Alexandra Craig; Margaret M. Cooper; Paul D. Paratore; Timothy C. Jenkins (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract